2019
DOI: 10.1101/871145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time and mode of Culicidae evolutionary history

Abstract: Mosquitoes are insects of medical importance due their role as vectors of different pathogens to humans and other mammals. There is a lack of information about the evolutionary history and phylogenetic positioning of the majority of mosquitoes species. Here we sequenced the mitogenomes of mosquitoes species through low-coverage sequencing and data mining. A total of 37 draft mitogenomes were assembled representing 11 genera and 16 of those were sequenced for the first time. The recovered mitogenomes showed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Furthermore, the phylogenic relationships of Toxorhynchites have not been fully determined [20,[29][30][31]. Although it was initially suggested that Toxorhynchites is an independent subfamily within Culicidae [32], subsequent reports placed it somewhere within the Culicinae subfamily [29,[33][34][35][36][37][38][39][40]. It would be interesting to understand if hematophagy was lost in Toxorhynchites or was an adaptation that arose in specific lineages after they diverged.…”
Section: Taxonomic Classificationmentioning
confidence: 99%
“…Furthermore, the phylogenic relationships of Toxorhynchites have not been fully determined [20,[29][30][31]. Although it was initially suggested that Toxorhynchites is an independent subfamily within Culicidae [32], subsequent reports placed it somewhere within the Culicinae subfamily [29,[33][34][35][36][37][38][39][40]. It would be interesting to understand if hematophagy was lost in Toxorhynchites or was an adaptation that arose in specific lineages after they diverged.…”
Section: Taxonomic Classificationmentioning
confidence: 99%
“…Spectacular findings, as traces of haemoglobin-derived porphyrins in the Eocene mosquito (Greenwalt et al, 2013) is very important proof of existence of blood-feeding behavior in Culicidae. Culicidae evolution, classification and internal relationships are still subject of debate (Reidenbach et al, 2009;Silva et al, 2019), and fossil records in addition to documenting the existence of extinct species, can often provide information on the behavior and ecology of ancient organisms. The coevolution of viruses with their hosts and vectors depends on the evolution of the hosts and vectors coupled with factors involved in virus evolution.…”
Section: Pementioning
confidence: 99%